2015
DOI: 10.1115/1.4031481
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Two-Phase Forced Cooling in Three-Dimensional Stacked Electronics: Technology Integration

Abstract: Three-dimensional (3D) stacked electronics present significant advantages from an electrical design perspective, ranging from shorter interconnect lengths to enabling heterogeneous integration. However, multitier stacking exacerbates an already difficult thermal problem. Localized hotspots within individual tiers can provide an additional challenge when the high heat flux region is buried within the stack. Numerous investigations have been launched in the previous decade seeking to develop cooling solutions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The comparison between the two sets of results is summarized in Table 2 with isopropanol as the carrier fluid and Table 3 with ethanol as the carrier fluid. In the tables, Ȳ and Z are calculated using eqn (1) and (2). At Re ≤ 1.29, the predicted bubble position from the simulations does not correspond to the experimental values.…”
Section: Validation Of Simulationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The comparison between the two sets of results is summarized in Table 2 with isopropanol as the carrier fluid and Table 3 with ethanol as the carrier fluid. In the tables, Ȳ and Z are calculated using eqn (1) and (2). At Re ≤ 1.29, the predicted bubble position from the simulations does not correspond to the experimental values.…”
Section: Validation Of Simulationsmentioning
confidence: 97%
“…1 A large number of studies have investigated the performance of these heat sinks for electronic cooling. [2][3][4][5] In the field of reactor engineering, variants of reactors including trickle-bed, 6 fluidized bed, 7 and bubble column reactors 8 rely on multiphase flows to enhance mass transport which requires a thorough understanding of their complex physics. Moreover, in most electrochemical sys-tems, gaseous products evolve at the interface of the electrodes and the electrolyte, including important processes such as water electrolysis, 9 chlor-alkali 10 and aluminum production.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of these regimes is expected to be linked to the ultra-small clearance of the geometry investigated, which confines bubble growth to an extent where only one flow regime, vapor plumes, was observed before dryout. Several studies [2,4,[6][7]24] have shown a similar phenomenon where the transition to annular convective flow boiling occurs at lower vapor qualities as the microgap height decreases due to increased bubble confinement.…”
Section: Quality Dependencementioning
confidence: 84%
“…Device features including micro pin fins, air trenches, ports and plenums were etched in silicon using Bosch process with high precision and accuracy. The microfabrication process flow for these devices was documented by Green et al [24].…”
Section: Experimental Testbedmentioning
confidence: 99%
“…Vapor-liquid phase change has always been of great interest in a wide range of technical applications, such as electronic cooling [1,2], chemical processes [3,4], space thermal control [5,6], microfluidic preparation [7,8], biomedical engineering [9,10], etc. As a typical technical application, a vapor chamber is recognized as one of the most effective ways to achieve uniform heat dissipation in a confined space due to its good temperature uniformity, flexible system compatibility, and high thermal transport capacity [11,12].…”
Section: Introductionmentioning
confidence: 99%